Analisis Kapasitas Produksi Unit Ammonia dan Urea Pabrik 1A (Studi Kapasitas Produksi pada Industri Pupuk) - Putra, Tri Adi; Furqon, Chairul (Universitas Brawijaya, Indonesia, 2015)
Capacity is the production, processing volume or the number of units that canproduced by a facility in a certain period. In 2013, PT. X through the mill 1A on ammoniaunit plan amounted to 296.300 tonnes of ammonia production, but production of ammoniaproduced as much as 260,910.61 tons while its design capacity of 365,000 tons and ureaproduction plan for 443,000 but as many as 384,275 tonnes of produced when its designcapacity of 629,625 tons. The difference in actual production capacity plan indicates thatthe factories 1A requires analysis of the production capacity in order to obtain strategicsteps to increase production. Models developed capacity analysis is to compare the actualcapacity of the capacity design, utility, efficiency, and capacity unused. The results thatproduced approximately 71.5% of its design capacity, production capacity lost due to annualmaintenance by 6.5% and due to the breakdown of 13% and unused production capacityby 9% of capacity its design. While the urea units that produce products in approximately61% of its design capacity, production capacity lost due to the annual maintenance of 2.5%and due to the break down of 13.5% and unused production capacity by 23% of its designcapacity.